Electrically reconfigurable terahertz signal processing devices using liquid metal components - Kimberly S. Reichel (Nature Portfolio, 2018)
Although there are many reports on the development of devices for terahertz signal processing, the possibility of electrical control of the functionality remains elusive. Here, the authors use electrically actuated liquid metal components incorporated into terahertz waveguides for controlling power flow and for frequency filtering.